(3HWdGf Mce GdeMce (B/s - (3GdLZHjQ, EHQGgje QVhGf HNjJs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2009)
(3jfbSe gPG GdcJGH Edi HGHjf hNGJeI JfGhd GdeDda GdHGH GdChd ef gPG GdcJGH hjMJhj aUdjf GdaUd GdChd JfGhd ajg eaghe Mce GdJMcje hWQb GdWYf ajg CeG GdaUd GdKGfj aJfGhd ajg GdbhGYO hGdCMcGe GdefXeI dOYhi HWdGf Mce GdJMcje CeG GdHGH GdKGfj abO JfGhd ajg MGdGJ hCSHGH HWdGf Mce GdeMce ef NdGd aUdjf hGdaUd GdChd(B: (3YQV ajg GdMGdGJ GdJj JDOj Edi HWdGf Mce GdeMce aj eQMdI GdEJaGb Ydi GdJMcje Ch GdeQMdI GdYbOjI CeG GdaUd GdKGfj(B: (3aYQV ajg GdMGdGJ GdJj jecf Cf JQO aj GdeQMdI GdELQGFjI(B. s
(3GdCUd CWQhMI (B((3OcJhQGg(B)-(3HETQGa dCSJGP GdOcJhQ jMj GdLed aj eYgO GdHMK hGdOQGSGJ GdYQHjI(B-(3eUQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B245-255.s
Keywords: (3GdJMcjes -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3fXQjI GdHWdGfs -- (3eUQs; (3fbV GdCMcGes -- (3eUQs